Maizy Chen's last chance - Yee, Lisa (Random House, 2022)
After her grandfather falls ill, eleven-year-old Maizy Chen travels to her mom's hometown of Last Chance, Minnesota, to help her grandparents run the Golden Palace, the family's Chinese restaurant. She is tasked with keeping Opa company while he recovers, and she soon finds herself learning about Lucky Chen, her great-great-grandfather who moved to Last Chance and opened the Golden Palace. She is shocked when the restaurant is targeted by a racist attack as they are the only Asian-American family in town, and she struggles with homesickness and mean girls. Luckily, Maizy makes a new friend and connects with her family's roots while learning that it's what's on the inside that counts.